2015
DOI: 10.1515/anre-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status among boys and girls of a central Indian Town (Sagar)

Abstract: The prevalence of undernutrition is a significant area of concern in many developing countries, where it is a major public health problem. The aim of the study was to assess the prevalence of undernutrition among school-going boys and girls of central Indian city Sagar, MP. A total of 612 individuals (312 girls and 300 boys) aged 5-18 years were examined and compared to the NCHS reference data. The nutritional status was assessed using following anthropometric indicators: body height and weight, body mass inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Mondal and Sen (50) assessed underweight, stunting, low BMI for age and its combinations in Indian schoolchildren between 5 and 12 years old, based on references from the patterns of the National Center of Health Statistics (51) . Following the same methodology, Thakur and Gautam (52) also analysed Indian school children between 5 and 18 years of age. The results obtained showed a great variability because of religious factors, ethnicity, geoclimatology and urban development.…”
Section: Discussionmentioning
confidence: 99%
“…Mondal and Sen (50) assessed underweight, stunting, low BMI for age and its combinations in Indian schoolchildren between 5 and 12 years old, based on references from the patterns of the National Center of Health Statistics (51) . Following the same methodology, Thakur and Gautam (52) also analysed Indian school children between 5 and 18 years of age. The results obtained showed a great variability because of religious factors, ethnicity, geoclimatology and urban development.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s and 1980s, these inequalities were observed even in direct measures of caloric intakes in poor households, apart from the quality of food consumed by both the poor and the rich, and in anthropometric and malnourishment indices (Agarwal 1989(Agarwal , 2014. Today the evidence on caloric intakes is more mixed, but other gender disadvantages persist, as observed in South Asia in terms of undernourished and underweight children (Thakur and Gautam 2015;Nuruddin and Hadden 2015). Moreover, globally, an estimated 613 million women are anaemic, especially but not only when pregnant and lactating (Gobal Nutrution Report 2017).…”
Section: < Insert Table 1 Near Here>mentioning
confidence: 99%
“…A similar result has also been found by Thakur and Gautam. 20 Z-score values of weight-for-age, height-forage and BMI-for-age revealed in their study among the school-going boys and girls of central Indian city Sagar, Madhya Pradesh that boys were more likely to be stunted than girls whereas girls were more likely to be underweight and undernourished than boys. Male children were found to be more prone to undernutrition than females as found in a study by Kabubo-Mariara et al, which indicated that boys are more likely than girls to suffer from chronic and acute undernutrition as well as underweight.…”
Section: Discussionmentioning
confidence: 92%
“…20 21 89±3.42 90.14±5.67 0.7747 12.67±1.93 12.5±1.5 0.3158 13.55±2.76 13.89±1.22 0.5145 4+ 28 20 98.04±4.45 98.3±3.06 0.2256 13.2±2.59 12.75±2.22 0.6289 13.64±1.79 13.93±0.13 0.7210 5+ 26 25 101.06±5.48 102.91±3.1 1.4758 15±3.20 14.83±3.4 0.1839 13.66±2.29 14.44±0.85 1.5999 6+ 30 32 104.5±4.87 105.5±4.3 0.8583 16.23±3.27 15.0±2.76 1.6041 13.67±0.96 14.17±1.38 1.6456 7+ 35 28 108.79±8.17 109.3±2.83 0.3151 18.6±3.31 17.5±2.12 1.5248 13.80±0.84 14.50±1.80 2.0423 8+ 40 29 112.36±5.75 113.25±4.33 0.7012 20.7±3.06 20.25±4.11 0.5217 13.92±1.36 14.85±2.30 2.1031 9+ 36 31 113.9±6.34 116.28±7.30 1.4285 22.64±2.75 21.58±2.23 1.7144 14.16±1.05 14.96±1.38 2.6906 92±4.02 119.95±8.22 1.9298 23.17±3.66 25.27±3.09 2.4755 52±1.64 15.01±1.35 1.3013…”
mentioning
confidence: 99%